Regeneration patterns of Cerasus leveilleana (Koehne) H. Ohba and C. jamasakura (Siebold ex Koidz.) H. Ohba in Satoyama forests of Sakuragawa City, Ibaraki Prefecture, Japan - KATSUDA, Kakeru; KAMIJO, Takashi; SAEKI, Ikuyo (Journal of the Japanese Society of Revegetation Technology, 2020)
Sakuragawa City is historically famous for its beautiful forested landscape with wild cherry blossoms. We surveyed the occurrence of saplings (dbh ≤ 9 cm) of the major cherry species Cerasus leveilleana and C. jamasakura, and identified the important factors facilitating their regeneration. Vegetation data of woody plants were collected from 36 square plots at 12 study sites in Sakuragawa. Three sites had a high density of saplings of the two species, especially C. leveilleana. According to GLMM analyses, the proportion of trees with sprouting stems had a positive relationship with sapling number. A high ratio of sprouting trees indicates the occurrence of harvesting disturbance in the past. Thus, traditional Satoyama management involving shortrotation cutting likely contributes to maintenance of landscape with wild cherry blossoms.